Social determinants and adherence to recommended COVID-19 vaccination among the Arab ethnic minority: A syndemics framework - Anat Amit Aharon (Frontiers in Public Health, 2022)
BackgroundSince the mass vaccination against SARS-CoV-2 was launched in Israel, the Arab ethnicity minority had lower vaccine uptake. The syndemics theory suggests a closely interrelated complex of health and social crises among vulnerable societies results in an increased disease burden or in more adverse health conditions. Syndemics may explain the health disparities between different people or communities. Likewise, acculturation was found to be associated with different health outcomes among minority populations. The purpose of the study is to explore the association between syndemic construct, acculturation style, and adherence to recommended COVID-19 vaccination among the Arab ethnicity in Israel.MethodsA cross-sectional study among 305 participants who completed a self-report questionnaire. Syndemic construct (syndemics score and syndemics severity) was calculated from the participants' health behavior index, self-rated health status, and adherence to flu vaccination. Four acculturation strategies were defined according to Barry's acculturation model: assimilation, integration, separation, and marginalization style. Linear regression (stepwise method) was conducted to determine the explanatory factors for COVID-19 vaccine adherence.ResultsAssimilation and separation acculturation styles and syndemics severity were significantly associated with higher adherence to the recommended COVID-19 vaccination (B = 1.12, 95%CI = 0.34–1.98; B = 0.45, 95%CI = 0.10–0.80; B = 0.18, 95%CI = 0.09–0.28; respectively). The explained variance of the model (R2) was 19.9%.ConclusionSyndemics severity, assimilation and separation acculturation styles were associated with higher adherence to recommended COVID-19 vaccination in the Israeli Arab minority population. Syndemics score was not associated with recommended COVID-19 vaccination. To encourage COVID-19 vaccination among minority communities, campaigns should be tailored to the social determinants in a sensitive and individualized manner.